Luiz Braga: uma fotografia da Caboquice? - Camargo, Alysson Barbosa (2023)
Luiz Braga carried out several aesthetic experiences during his career, ranging from his black and white recordings to his color photographs, as well as his Night Vision series. However, color isn’t the only aspect appearing in his work since it is in an intimate dialogue with “Caboquice”. Furthermore, this research will make a dialogue between the photographic of the artist and the Caboquice category on Marajo Island -PA from a socio-anthropological approach.